“PEMANFAATAN COMIC STRIPS UNTUK MENULIS CERITA PENDEK BAGI ANAK-ANAK USIA SEKOLAH DASAR” - Novi Rahmania; Rudi Umar Susanto (JA (Jurnal Abdiku) : Jurnal Pengabdian Kepada Masyarakat, 2022)
In the 2nd year of the Covid-19 pandemic, the impact on the world of education is increasingly felt. Everything happens so fast that constant adjustments are needed. Among them, how to keep students motivated to learn online. It is undeniable that online learning clearly has differences with face-to-face learning, which places more emphasis on face-to-face interactions between teachers and students, as well as between students. This is where the boredom of online learning sometimes arises. The community service team that we founded aims to make use of comic strips to write short stories, which will increase student motivation and reduce boredom, because it invites students to learn more and develop creativity by writing in an interesting process.